2002
DOI: 10.1152/ajpendo.00085.2002
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific effects of chronic dietary leucine and norleucine supplementation on protein synthesis in rats

Abstract: Acute administration of leucine and norleucine activates the mammalian target of rapamycin (mTOR) cell-signaling pathway and increases rates of protein synthesis in a number of tissues in fasted rats. Although persistent stimulation of mTOR signaling is thought to increase protein synthetic capacity, little information is available concerning the effects of chronic administration of these agonists on protein synthesis, mTOR signal transduction, or leucine metabolism. Hence, we developed a model of chronic leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
102
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 71 publications
(74 reference statements)
11
102
1
9
Order By: Relevance
“…Of the BCAAs, leucine appears to be the specific effector in protein synthesis in several tissues, including skeletal muscle, liver, and adipose tissue. 7,8) In the present study, we found that excess intake of leucine induced SDH activity with increased amounts of SDH mRNA.…”
supporting
confidence: 63%
“…Of the BCAAs, leucine appears to be the specific effector in protein synthesis in several tissues, including skeletal muscle, liver, and adipose tissue. 7,8) In the present study, we found that excess intake of leucine induced SDH activity with increased amounts of SDH mRNA.…”
supporting
confidence: 63%
“…The increase in amino acid utilization and protein synthesis in the HQ, but not in the PDV, was mediated largely by the regional increase in blood flow. Interestingly, recent studies have shown that adipose tissue protein synthesis is highly responsive to nutrient stimulation (31,32). Because ST induces a repartitioning of nutrients away from adipose tissue and toward lean tissue deposition (19), we postulate that the lack of ST-induced stimulation of whole body protein synthesis in the fed state may, in part, be due to an ST-induced suppression of the feeding-induced stimulation of protein synthesis in adipose tissue.…”
Section: Discussionmentioning
confidence: 85%
“…protein synthesis, particularly by stimulating the activity of proteins involved in the translation process, which is critical for cells to control protein synthesis (Anthony et al, 2001;Lynch, Hutson, Patson, 2002a;Crozier et al, 2005;Garlick, 2005;. This modulation may involve the activation of specific intracellular pathways involved in protein synthesis, including activation of the mammalian target of rapamycin (mTOR) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the benefits promoted by this diet on body composition can be attributed to high consumption of branched-chain aminoacids (BCAA), which include the aminoacids leucine, valine and isoleucine (Donato et al, 2004;Layman, Walker, 2006;Katsanos et al, 2006). According to this hypothesis, high protein consumption not only increases the availability of substrates (aminoacids) for protein synthesis, but also stimulates anabolic processes observed after high protein consumption (Campos et al, 1999).Leucine has been shown to modulate the rate ofprotein synthesis, particularly by stimulating the activity of proteins involved in the translation process, which is critical for cells to control protein synthesis (Anthony et al, 2001;Lynch, Hutson, Patson, 2002a;Crozier et al, 2005;Garlick, 2005;. This modulation may involve the activation of specific intracellular pathways involved in protein synthesis, including activation of the mammalian target of rapamycin (mTOR) pathway.…”
mentioning
confidence: 99%